PENGARUH ENVIRONMENTAL KNOWLEDGE DAN GREEN MARKETING TERHADAP PURCHASE INTENTION DENGAN MEDIASI ENVIRONMENTAL ATTITUDE PADA KOPI STARBUCKS - Selin Faradina; Yuniarti Fihartini; Roslina Roslina (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the effects of Environmental Knowledge and Green Marketing on Purchase Intention, with Environmental Attitude serving as a mediating variable among Starbucks consumers. This research employed a quantitative approach using a survey method. Data were collected from 210 respondents who met the predetermined criteria and were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that environmental knowledge has a positive and significant effect on both environmental attitude and purchase intention. Similarly, green marketing positively and significantly influences environmental attitude and purchase intention. Furthermore, environmental attitude has a positive and significant effect on purchase intention. The mediation analysis demonstrates that environmental attitude significantly mediates the relationships between environmental knowledge and purchase intention, as well as between green marketing and purchase intention. These findings indicate that increasing consumers’ environmental knowledge and implementing effective green marketing strategies can foster more positive environmental attitudes, which in turn enhance consumers’ intention to purchase Starbucks products. This study provides practical implications for companies to strengthen environmental education initiatives and consistently implement green marketing strategies to increase consumer purchase intention while supporting sustainable business practices.